Semantics and function of kinesic means in speech process - Kortabaeva, G. K.; Mukhambetzhanova, K. T. (Journal of Oriental Studies, 2016)
In this article it is considered about kinesic means in the kazakh language, their semantics, function in speech process and proverbs- sayings.